2017
DOI: 10.1158/1078-0432.ccr-17-0133
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Medicine–Based Approach to Model Patterns of Chemoresistance and Tumor Recurrence Using Ovarian Cancer Stem Cell Spheroids

Abstract: Chemoresistant ovarian cancers grow in suspension within the ascites fluid. To screen the effect of chemotherapeutics and biologics on resistant ovarian cancers with a personalized basis, we developed a 3D hanging drop spheroid platform. We initiated spheroids with primary aldehyde dehydrogenase-positive (ALDH) CD133 ovarian cancer stem cells (OvCSC) from different patient samples and demonstrated that stem cell progeny from harvested spheroids was similar to the primary tumor. OvCSC spheroids were utilized to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 46 publications
3
107
0
1
Order By: Relevance
“…With this combinatory approach, it will be possible to gain a more complete picture of the cancer microenvironment and ascertain potential avenues of treatment. Additionally, non-cell factors such as chemotaxis, 130 3D culture 94,[131][132][133][134][135][136] , and hypoxia 137 should be considered for future investigations, in conjunction with mechanical cues to create a microenvironment that can more fully recapitulate in vivo conditions. The study of ovarian cancer mechanotransduction promises to improve patient treatment through future investigations that utilize designs pertinent to the specific microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…With this combinatory approach, it will be possible to gain a more complete picture of the cancer microenvironment and ascertain potential avenues of treatment. Additionally, non-cell factors such as chemotaxis, 130 3D culture 94,[131][132][133][134][135][136] , and hypoxia 137 should be considered for future investigations, in conjunction with mechanical cues to create a microenvironment that can more fully recapitulate in vivo conditions. The study of ovarian cancer mechanotransduction promises to improve patient treatment through future investigations that utilize designs pertinent to the specific microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct responses to therapy were observed in distinct primary tumor xenografts similar to those observed in spheroids. Spheroids resistant to Cisplatin/ALDH inhibitor therapy had persistent, albeit lower ALDH expression and complete loss of CD133 expression while those resistant to cisplatin/JAK2 inhibitor therapy were enriched for ALDH+ cells [54].…”
Section: The Role Of Crc Stem Cells As Biomarkers For Crc Personalizmentioning
confidence: 97%
“…measures to change biomarker expression lead to the corresponding change in treatment response. In other words, a strong association between biomarker and treatment outcome should result from a similar direct treatment effect on both, biomarker level and endpoint of therapy [54].…”
Section: The Role Of Crc Stem Cells As Biomarkers For Crc Personalizmentioning
confidence: 99%
“…The results showed that globular stem cells sustain their resistance to cisplatin/ALDH inhibitor, although the expression of ALDH is low, and that of CD133 is completely lost. However, spheres resistant to cisplatin/JAK2 inhibitors have enriched ALDH+91 cells [35]. In the above-mentioned studies, the culture of spheroids originated from the ascites in the late stage of cancer.…”
Section: Spheroidmentioning
confidence: 99%